Sistem Rantai Pasok Industri Minuman Softdrink - Yossy Kartika (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2011)
This paper discussed the supply chain management solutions at PT Coca Cola Bottling Indonesia withan evaluation of supply chain management of Coca Cola, where supply chain management is aconcept or mechanism to increase the total productivity of companies in the supply chain throughoptimization of the time, location and quantity of flow materials from raw materials into semi-finishedproducts and finished products. Supply Chain Management is not only about the relationship with thesupplier but also the link between the company and consumers. By knowing the value of theperformance of supply chainnya the company can improve the effectiveness and productivity of theorganization to achieve organizational goals is to win the competition, and increase corporate profits.In such measurements should be made an integrated framework and must comply with theconditions of the studied companies.